Feasibility of using integrated fingerprinting, profiling and chemometrics approach to understand (bio) chemical changes throughout commercial red winemaking: A case study on Merlot. (January 2020) - Arcena, Mylene Ross; Kebede, Biniam; Leong, Sze Ying; Silcock, Patrick; Oey, Indrawati
Graphical abstract: Highlights: Multiplatform analytical approach was used to study chemical changes of winemaking. Merlot musts at premaceration were rich in green odourant volatile compounds. Phenolics and volatiles are more extracted during maceration-alcoholic fermentation. Complex enzymatic and oxidation changes occur during malolactic fermentation. The final wine is rich in phenolic acids, esters, alcohols and terpenes. Abstract: This study assessed the feasibility of using a multiplatform approach; integrating untargeted fingerprinting of volatiles and targeted profiling of phenolic and oenological attributes (soluble solids, pH, titratable acidity and colour properties) coupled with chemometrics to understand complex (bio) chemical reactions occurring during Merlot red winemaking. The changes were investigated at three winemaking stages, starting from pre-maceration (PM), maceration-alcoholic fermentation (MAF) up to completion of malolactic fermentation (MLF). Merlot musts at PM were characterised by lighter colour and higher amount of green aroma-related volatiles. Completion of MAF led to increased extraction of anthocyanins, flavonols, and stilbenes, resulting in a more intense and darker fermenting juice. Furthermore, development of yeast-fermentation associated volatiles such as esters and alcohols was observed at this stage. The final wine, when MLF was completed, was rich in phenolic acids, esters, alcohols, and terpenes. The multiplatform analytical approach was effective to unravel the complex reactions throughout Merlot winemaking process and find relevant markers, which could help to predict expected quality attributes in the finished wine.